Effects of Real-Time High Temperature and Loading Rate on Deformation and Strength Behavior of Granite - YiFeng Zhang; Fan Zhang; Ke Yang; ZhengYu Cai (Geofluids)
Knowledge of deformation and strength behavior of rocks under high in situ temperature is highly important for the control of geological disasters in exploration of hot dry rock and mining in deep formation. In this study, uniaxial compression tests were carried out on granite under different real-time high-temperature conditions (25, 200, 300, 400, 500, 600, and 700°C) and loading rates (0.01, 0.1, and 0.5 mm/min). The effects of real-time high temperature and loading rate on the uniaxial compressive strength and elastic modulus of granite were studied, and the microscopic morphology of the fracture surface was analyzed. The results show that the uniaxial compressive strength and elastic modulus of granite increase first and then decrease with the increase of temperature. The uniaxial compressive strength clearly increases at 200°C and decreases gradually when the temperature exceeds 300°C. Under the same temperature conditions, the uniaxial compressive strength of granite decreases and the elastic modulus increases with increasing loading rate. When the temperature reaches 600°C, the effect of the loading rate on the uniaxial compressive strength and elastic modulus of granite decreases significantly. The test results are compared with the results of work performed on quenched granite. Under real-time high-temperature conditions, the thermal crack effect has a significant influence on the uniaxial compressive strength and elastic modulus of granite, without the thermal hardening effect of quenched granite. During hydraulic fracturing, the rock skeleton near the injection well is cooled and shrunk, as is the thermal hardening effect caused by high-temperature quenching. The formation of thermal equilibrium leads to the large-scale extension of fracture cracks along the weak plane structure, such as the effect of thermal cracks on granite under real-time high-temperature conditions.